The Contribution of the Islamic-Integrated 9E Learning Cycle Model to Students’ Scientific Literacy - Raicha Oktafiani; Bella Satiyo Putri; Aryani Dwi Kesumawardani (Yayasan Darussalam Bengkulu, 2025)
This study aims to examine the contribution of the Islamic value-integrated 9E Learning Cycle model to students’ scientific literacy in secondary science education. A quasi-experimental design with a pretest-posttest control group was employed, involving two intact classes selected through cluster random sampling, where the experimental group was taught using the 9E Learning Cycle integrated with Islamic values and the control group received conventional instruction. Data were collected using a validated scientific literacy test, observation sheets, and questionnaires, and analyzed through descriptive statistics, normalized gain (N-gain), independent samples t-test, Pearson correlation, and linear regression at a significance level of 0.05. The results revealed that the experimental group achieved higher posttest scores and a moderate N-gain (0.59) compared to the control group (0.34), with statistically significant differences (p < 0.05). Furthermore, correlation and regression analyses indicated a positive relationship between the learning model and scientific literacy, with a contribution of 17.3% to learning outcomes. These findings suggest that the integration of the 9E Learning Cycle with Islamic values effectively enhances students’ ability to interpret scientific phenomena, evaluate evidence, and apply scientific reasoning, while also fostering meaningful engagement in learning. In conclusion, the study confirms that a constructivist learning model enriched with value-based integration can simultaneously improve cognitive and affective dimensions of learning. The implications of this study highlight the importance of designing science instruction that integrates inquiry-based learning with ethical and cultural values to support holistic education and strengthen scientific literacy in diverse educational contexts.